Thermal analysis of chitin in different aging of Leucaena leucocephala pods: article - Ismail, Muhammad Shahid; Abd Razak., Noorharliza (2016)
In this work, the thermal analysis of chitin with different aging of Leucaena leucocephala pod were investigated by means of thermogravimetry analyses and differential scanning calorimetry under dynamic nitrogen atmosphere in the range of 25⁰C-500⁰C. The samples also have been test with chromameter to find the colour characteristic. The results obtained were compared with literature to find the similarities of the chitin characteristic. From results, the different aging of samples gives a slightly different curve for TGA and DSC. The first stage of mass loss was at temperature between 50 to 100⁰C while the second stage mass loss is between 150 to 450⁰C. The maximum degradation temperature (DTGmax) was observed at between 300 to 350⁰C for all the samples. Subsantially, the two phase mass loss and temperature at DTGmax in thermogravimetry analysis showed a similar characteristic of chitin reported from several previous studies. In Differential scanning calorimetry, the samples melting temperature (Tm) was recorded as close to each other which are 90 ⁰C. However, melting enthalpy (ΔHm) showed a value that is distinct for each sample. This may due to the different chemical composition from each sample. Therefore, further study can be made to know better the chitin characteristic from this sample with different type of analysis.